Elastogenic Protein Expression of a Highly Elastic Murine Spinal Ligament: The Ligamentum Flavum - Brown, Jeffrey P.; Lind, Rachel M.; Burzesi, Anthony F.; Kuo, Catherine K. (PLOS ONE, 2012)
Spinal ligaments, such as the ligamentum flavum (LF), are prone to degeneration and iatrogenic injury that can lead to back pain and nerve dysfunction. Repair and regeneration strategies for these tissues are lacking, perhaps due to limited understanding of spinal ligament formation, the elaboration of its elastic fibers, maturation and homeostasis. Using immunohistochemistry and histology, we investigated murine LF elastogenesis and tissue formation from embryonic to mature postnatal stages. We characterized the spatiotemporal distribution of the key elastogenic proteins tropoelastin, fibrillin-1, fibulin-4 and lysyl oxidase. We found that elastogenesis begins in utero with the microfibril constituent fibrillin-1 staining intensely just before birth. Elastic fibers were first detected histologically at postnatal day (P) 7, the earliest stage at which tropoelastin and fibulin-4 stained intensely. From P7 to P28, elastic fibers grew in diameter and became straighter along the axis. The growth of elastic fibers coincided with intense staining of tropoelastin and fibulin-4 staining, possibly supporting a chaperone role for fibulin-4. These expression patterns correlated with reported skeletal and behavioral changes during murine development. This immunohistochemical characterization of elastogenesis of the LF will be useful for future studies investigating mechanisms for elastogenesis and developing new strategies for treatment or regeneration of spinal ligaments and other highly elastic tissues.